The mechanisms of sleep restriction therapy for insomnia disorder - Maurer, LF (2020)
Insomnia is one of the most common health burdens world-wide. While pharmacological treatment is available, the current recommended first-line intervention is a multi-component psychological therapy called cognitive behavioural therapy for insomnia (CBT-I). Although randomised-controlled trials support the efficacy of CBT-I, its treatment mechanisms are not well understood.